Attracting PhDs to K-12 Education: A Demonstration Program for Science, Mathematics, and Technology - National Research Council (The National Academies Press, 2002)
The National Research Council (NRC) has undertaken a three-phase project to explore the possibility of a program to attract science, mathematics and engineering PhDs to careers in K-12 education. The first phase of the project surveyed the interests of recent PhDs in science and mathematics in pursuing careers in secondary education. Analysis of the Phase I data suggests that a significant percentage of PhDs might be interested in pursuing careers in secondary education under some circumstances. This report from the second phase of the project presents a proposal for a national demonstration program to determine how one might prepare PhDs to be productive members of the K-12 education community. The proposed program is designed to help meet the needs of the nation's schools, while providing further career opportunities for recent PhDs in science, mathematics and engineering.
Keywords: Education

Proposed Framework for Evaluating the Safety of Dietary Supplements -- For Comment - Institute of Medicine (The National Academies Press, 2002)
Keywords: Food and Nutrition

Investigating the Influence of Standards: A Framework for Research in Mathematics, Science, and Technology Education - National Research Council (The National Academies Press, 2002)
Since 1989, with the publication of Curriculum and Evaluation Standards for Mathematics by the National Council of Teachers of Mathematics, standards have been at the forefront of the education reform movement in the United States. The mathematics standards, which were revised in 2000, have been joined by standards in many subjects, including the National Research Council's National Science Education Standards published in 1996 and the Standards for Technical Literacy issued by the International Technology Education Association in 2000. There is no doubt that standards have begun to influence the education system. The question remains, however, what the nature of that influence is and, most importantly, whether standards truly improve student learning. To answer those questions, one must begin to examine the ways in which components of the system have been influenced by the standards. Investigating the Influence of Standards provides a framework to guide the design, conduct, and interpretation of research regarding the influences of nationally promulgated standards in mathematics, science, and technology education on student learning. Researchers and consumers of research such as teachers, teacher educators, and administrators will find the framework useful as they work toward developing an understanding of the influence of standards.
Keywords: Education

Incorporating ITS Into the Transportation Planning Process: An Integrated Planning Framework (ITS, M&O, Infrastructure) Executive Guidebook - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2002)
TRB’s National Cooperative Highway Research Program (NCHRP) Web-Only Document 118, Part I: Incorporating ITS Into the Transportation Planning Process: An Integrated Planning Framework (ITS, M&O, Infrastructure) Executive Guidebook explores factors that are pushing regions and states towards integration of intelligent transportation systems in the transportation planning process, including the institutional, organizational, and technical processes that are included within it. In addition, this report examines challenges, transition strategies, and resources available to help agencies interested in adopting the integrated framework concept. This report is summary of the full report that was published as NCHRP Web-Only Document 118, Part II.
Keywords: Transportation and Infrastructure

Incorporating ITS Into the Transportation Planning Process: An Integrated Planning Framework (ITS, M&O, Infrastructure) Practitioner's Guidebook - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2002)
TRB’s National Cooperative Highway Research Program (NCHRP) Web-Only Document 118, Part II: Incorporating ITS Into the Transportation Planning Process: An Integrated Planning Framework (ITS, M&O, Infrastructure) Practitioner’s Guidebook explores factors that are pushing regions and states towards integration of intelligent transportation systems in the transportation planning process, including the institutional, organizational, and technical processes that are included within it. In addition, this report examines challenges, transition strategies, and resources available to help agencies interested in adopting the integrated framework concept. A companion overview of this report has been published as NCHRP Web-Only Document 118 Part I.
Keywords: Transportation and Infrastructure

Natural Disasters and Energy Policy: A Summary of the Forum on Natural Diasters and Energy Policy, June 12, 2001, Washington, DC - National Research Council (The National Academies Press, 2002)
Keywords: Earth Sciences

Enhancing Undergraduate Learning with Information Technology: A Workshop Summary - National Research Council (The National Academies Press, 2002)
Enhancing Undergraduate Learning with Information Technology reports on a meeting of scientists, policy makers, and researchers convened to discuss new approaches to undergraduate science, mathematics, and technology education. The goal of the workshop was to inform workshop participants and the public about issues surrounding the use of information technology in education. To reach this goal, the workshop participants paid particular attention to the following issues: What educational technologies currently exist and how they are being used to transform undergraduate science, engineering, mathematics, and technology education; What is known about the potential future impact of information technology on teaching and learning at the undergraduate level; How to evaluate the impact of information technology on teaching and learning; and What the future might hold.
Keywords: Education

Community Programs to Promote Youth Development - National Research Council; Institute of Medicine (The National Academies Press, 2002)
After-school programs, scout groups, community service activities, religious youth groups, and other community-based activities have long been thought to play a key role in the lives of adolescents. But what do we know about the role of such programs for today's adolescents? How can we ensure that programs are designed to successfully meet young people's developmental needs and help them become healthy, happy, and productive adults? Community Programs to Promote Youth Development explores these questions, focusing on essential elements of adolescent well-being and healthy development. It offers recommendations for policy, practice, and research to ensure that programs are well designed to meet young people's developmental needs. The book also discusses the features of programs that can contribute to a successful transition from adolescence to adulthood. It examines what we know about the current landscape of youth development programs for America's youth, as well as how these programs are meeting their diverse needs. Recognizing the importance of adolescence as a period of transition to adulthood, Community Programs to Promote Youth Development offers authoritative guidance to policy makers, practitioners, researchers, and other key stakeholders on the role of youth development programs to promote the healthy development and well-being of the nation's youth.
Keywords: Behavioral and Social Sciences; Health and Medicine

Reducing Suicide: A National Imperative - Institute of Medicine (The National Academies Press, 2002)
Every year, about 30,000 people die by suicide in the U.S., and some 650,000 receive emergency treatment after a suicide attempt. Often, those most at risk are the least able to access professional help. Reducing Suicide provides a blueprint for addressing this tragic and costly problem: how we can build an appropriate infrastructure, conduct needed research, and improve our ability to recognize suicide risk and effectively intervene. Rich in data, the book also strikes an intensely personal chord, featuring compelling quotes about people’s experience with suicide. The book explores the factors that raise a person’s risk of suicide: psychological and biological factors including substance abuse, the link between childhood trauma and later suicide, and the impact of family life, economic status, religion, and other social and cultural conditions. The authors review the effectiveness of existing interventions, including mental health practitioners’ ability to assess suicide risk among patients. They present lessons learned from the Air Force suicide prevention program and other prevention initiatives. And they identify barriers to effective research and treatment. This new volume will be of special interest to policy makers, administrators, researchers, practitioners, and journalists working in the field of mental health.
Keywords: Health and Medicine

Down to Earth: Geographic Information for Sustainable Development in Africa - National Research Council (The National Academies Press, 2002)
In 1992, world leaders adopted Agenda 21, the work program of the 1992 U.N. Conference on Environment and Development. This landmark event provided a political foundation and action items to facilitate the global transition toward sustainable development. The international community marked the tenth anniversary of this conference in Johannesburg, South Africa, in August 2002. Down to Earth, a component of the U.S. State Department's "Geographic Information for Sustainable Development" project for the World Summit, focuses on sub-Saharan Africa with examples drawn from case-study regions where the U.S. Agency for International Development and other agencies have broad experience. Although African countries are the geographic focus of the study, the report has broader applicability. Down to Earth summarizes the importance and applicability of geographic data for sustainable development and draws on experiences in African countries to examine how future sources and applications of geographic data could provide reliable support to decision-makers as they work towards sustainable development. The committee emphasizes the potential of new technologies, such as satellite remote-sensing systems and geographic information systems, that have revolutionized data collection and analysis over the last decade.
Keywords: Earth Sciences; Environment and Environmental Studies

Health Insurance is a Family Matter - Institute of Medicine (The National Academies Press, 2002)
Health Insurance is a Family Matter is the third of a series of six reports on the problems of uninsurance in the United Sates and addresses the impact on the family of not having health insurance. The book demonstrates that having one or more uninsured members in a family can have adverse consequences for everyone in the household and that the financial, physical, and emotional well—being of all members of a family may be adversely affected if any family member lacks coverage. It concludes with the finding that uninsured children have worse access to and use fewer health care services than children with insurance, including important preventive services that can have beneficial long-term effects.
Keywords: Health and Medicine

The Disposition Dilemma: Controlling the Release of Solid Materials from Nuclear Regulatory Commission-Licensed Facilities - National Research Council (The National Academies Press, 2002)
The U.S. Nuclear Regulatory Commission (USNRC) and its predecessor, the U.S. Atomic Energy Commission (AEC), have attempted since the 1970s to give greater uniformity to the policy and regulatory framework that addresses the disposition of slightly radioactive solid material. The issue remains unresolved and controversial. The USNRC has tried to issue policy statements and standards for the release of slightly radioactive solid material from regulatory control, while such material has been released and continues to be released under existing practices. In 1980 the USNRC proposed regulatory changes to deregulate contaminated metal alloys but withdrew them in 1986 and began work with the Environmental Protection Agency (EPA) to develop more broadly applicable federal guidance. In 1990 the USNRC issued a more sweeping policy, as directed by the Low Level Radioactive Waste Policy Amendments Act of 1985 (LLWPAA), declaring materials with low concentrations of radioactivity contamination "below regulatory concern" (BRC) and hence deregulated. Congress intervened to set aside the BRC policy in the Energy Policy Act of 1992, after the USNRC's own suspension of the policy. Subsequent attempts by USNRC staff to build consensus among stakeholder groups as a basis for future policy articulations were met by boycotts of stakeholder meetings, both in the immediate aftermath of the BRC policy and again in 1999 during public hearings on a new examination of the disposition of such materials. The only USNRC standard addressing the disposition of slightly radioactive solid material is a guidance document published in June 1974 by the AEC, whose regulatory authority over civilian nuclear facilities the USNRC assumed upon its creation a few months later in January 1975. In August 2000, with another examination of this issue under way, the USNRC requested that the National Research Council form a committee to provide advice in a written report. The National Research Council established the Committee on Alternatives for Controlling the Release of Solid Materials from Nuclear Regulatory Commission-Licensed Facilities to address this task. The committee's task involved evaluating and providing recommendations on the history of the technical bases and policies and precedents for managing slightly radioactive solid material from USNRC-licensed facilities; the sufficiency of technical bases needed to establish standards for release of solid materials from regulatory control ("clearance standards") and the adequacy of measurement technologies; the concerns of stakeholders and how the USNRC should incorporate them; and the efforts of international organizations on clearance standards. The committee was also asked to examine the current system for release of slightly radioactive solid material from regulatory control, to recommend whether the USNRC should continue to use this system and to recommend changes if appropriate. The committee's fact-finding process included two site visits to waste brokering facilities and nearly 40 invited presentations from the USNRC, the U.S. Department of Energy (DOE), and EPA staff; stakeholder organizations; nuclear industry organizations; and other interested parties. In conducting its study, the committee first examined the current system of standards, guidance, and practices used by the USNRC and agreement states to determine whether to release slightly radioactive solid material from further regulatory control under the Atomic Energy Act. The committee found that the current, workable system allows licensees to release material according to pre-established criteria but contains inconsistencies such that nuclear reactor licensees can release materials only if there is no detectable radioactivity (above background levels), whereas materials licensees can do so if small detectable levels are found. The committee evaluated technical analyses of the estimated doses of the final disposition of slightly radioactive solid materials. These analyses were conducted by federal agencies and international organizations, including the International Atomic Energy Agency (IAEA), the European Commission, and other groups. The Disposition Dilemma:Controlling the Release of Solid Materials from Nuclear Regulatory Commission-Licensed Facilities explains the committee's findings and recommendations.
Keywords: Environment and Environmental Studies

Improving Learning with Information Technology: Report of a Workshop - National Research Council (The National Academies Press, 2002)
In spring 2000, representatives from the U.S. Department of Education (DOEd) and senior staff at the National Research Council (NRC) recognized a common frustration: that the potential of information technology to transform K-12 education remains unrealized. In fall 2000 the U.S. DOEd formally requested that the National Academies undertake an interdisciplinary project called Improving Learning with Information Technology (ILIT). The project was launched with a symposium on January 24-25, 2001. This report summarizes the proceedings of the symposium and is intended for people interested in considering better strategies for using information technology in the educational arena. While it offers insights from the presenters on both the challenges to and the opportunities for forging a better dialogue among learning scientists, technologists, and educators, it does not contain conclusions or recommendations. Rather, it highlights issues to consider, constituents to engage, and strategies to employ in the effort to build a coalition to harness the power of information technologies for the improvement of American education. Every effort has been made to convey the speakers' content and viewpoints accurately. Recognizing the speculative nature of many of the speaker contributions, most attributions identify a speaker by area of expertise rather than by name. The report reflects the proceedings of the workshop and is not intended to be a comprehensive review of all the issues involved in the project to improve learning with information technology.
Keywords: Education

Dietary Risk Assessment in the WIC Program - Institute of Medicine (The National Academies Press, 2002)
Dietary Risk Assessment in the WIC Program reviews methods used to determine dietary risk based on failure to meet Dietary Guidelines for applicants to the Special Supplemental Nutrition Program for Women, Infants, and Children (WIC). Applicants to the WIC program must be at nutritional risk to be eligible for program benefits. Although “dietary risk” is only one of five nutrition risk categories, it is the category most commonly reported among WIC applicants. This book documents that nearly all low-income women in the childbearing years and children 2 years and over are at risk because their diets fail to meet the recommended numbers of servings of the food guide pyramid. The committee recommends that all women and children (ages 2-4 years) who meet the eligibility requirements based on income, categorical and residency status also be presumed to meet the requirement of nutrition risk. By presuming that all who meet the categorical and income eligibility requirements are at dietary risk, WIC retains its potential for preventing and correcting nutrition-related problems while avoiding serious misclassification errors that could lead to denial of services for eligible individuals.
Keywords: Food and Nutrition

Technically Speaking: Why All Americans Need to Know More About Technology - National Academy of Engineering; National Research Council (The National Academies Press, 2002)
Cell phones . . . airbags . . . genetically modified food . . . the Internet. These are all emblems of modern life. You might ask what we would do without them. But an even more interesting question might be what would we do if we had to actually explain how they worked? The United States is riding a whirlwind of technological change. To be sure, there have been periods, such as the late 1800s, when new inventions appeared in society at a comparable rate. But the pace of change today, and its social, economic, and other impacts, are as significant and far reaching as at any other time in history. And it seems that the faster we embrace new technologies, the less we’re able to understand them. What is the long-term effect of this galloping technological revolution? In today’s new world, it is nothing less than a matter of responsible citizenship to grasp the nature and implications of technology. Technically Speaking provides a blueprint for bringing us all up to speed on the role of technology in our society, including understanding such distinctions as technology versus science and technological literacy versus technical competence. It clearly and decisively explains what it means to be a technologically-literate citizen. The book goes on to explore the context of technological literacy—the social, historical, political, and educational environments. This readable overview highlights specific issues of concern: the state of technological studies in K-12 schools, the reach of the Internet into our homes and lives, and the crucial role of technology in today’s economy and workforce. Three case studies of current issues—car airbags, genetically modified foods, and the California energy crisis—illustrate why ordinary citizens need to understand technology to make responsible decisions. This fascinating book from the National Academy of Engineering is enjoyable to read and filled with contemporary examples. It will be important to anyone interested in understanding how the world around them works.
Keywords: Health and Medicine; Engineering and Technology

Scientific and Medical Aspects of Human Reproductive Cloning - National Research Council (The National Academies Press, 2002)
Human reproductive cloning is an assisted reproductive technology that would be carried out with the goal of creating a newborn genetically identical to another human being. It is currently the subject of much debate around the world, involving a variety of ethical, religious, societal, scientific, and medical issues. Scientific and Medical Aspects of Human Reproductive Cloning considers the scientific and medical sides of this issue, plus ethical issues that pertain to human-subjects research. Based on experience with reproductive cloning in animals, the report concludes that human reproductive cloning would be dangerous for the woman, fetus, and newborn, and is likely to fail. The study panel did not address the issue of whether human reproductive cloning, even if it were found to be medically safe, would be—or would not be—acceptable to individuals or society.
Keywords: Biology and Life Sciences; Health and Medicine

Coal Waste Impoundments: Risks, Responses, and Alternatives - National Research Council (The National Academies Press, 2002)
On October 11, 2000, a breakthrough of Martin County Coal Corporation’s coal waste impoundment released 250 million gallons of slurry in near Inez, Kentucky. The 72-acre surface impoundment for coal processing waste materials broke through into a nearby underground coal mine. Although the spill caused no loss of human life, environmental damage was significant, and local water supplies were disrupted. This incident prompted Congress to request the National Research Council to examine ways to reduce the potential for similar accidents in the future. This book covers the engineering practices and standards for coal waste impoundments and ways to evaluate, improve, and monitor them; the accuracy of mine maps and ways to improve surveying and mapping of mines; and alternative technologies for coal slurry disposal and utilization. The book contains advice for multiple audiences, including the Mine Safety and Health Administration, the Office of Surface Mining, and other federal agencies; state and local policymakers and regulators; the coal industry and its consultants; and scientists and engineers.
Keywords: Environment and Environmental Studies

Environmental Effects of Transgenic Plants: The Scope and Adequacy of Regulation - National Research Council (The National Academies Press, 2002)
Transgenic crops offer the promise of increased agricultural productivity and better quality foods. But they also raise the specter of harmful environmental effects. In this new book, a panel of experts examines: • Similarities and differences between crops developed by conventional and transgenic methods • Potential for commercialized transgenic crops to change both agricultural and nonagricultural landscapes • How well the U.S. government is regulating transgenic crops to avoid any negative effects. Environmental Effects of Transgenic Plants provides a wealth of information about transgenic processes, previous experience with the introduction of novel crops, principles of risk assessment and management, the science behind current regulatory schemes, issues in monitoring transgenic products already on the market, and more. The book discusses public involvement—and public confidence—in biotechnology regulation. And it looks to the future, exploring the potential of genetic engineering and the prospects for environmental effects.
Keywords: Agriculture; Biology and Life Sciences

Integrity in Scientific Research: Creating an Environment That Promotes Responsible Conduct - Institute of Medicine; National Research Council (The National Academies Press, 2002)
"Most people say that it is the intellect which makes a great scientist. They are wrong: it is character."—Albert Einstein Integrity in Scientific Research attempts to define and describe those elements that encourage individuals involved with scientific research to act with integrity. Recognizing the inconsistency of human behavior, it stresses the important role that research institutions play in providing an integrity—rich environment, citing the need for institutions to provide staff with training and education, policies and procedures, and tools and support systems. It identifies practices that characterize integrity in such areas as peer review and research on human subjects and weighs the strengths and limitations of self—evaluation efforts by these institutions. In addition, it details an approach to promoting integrity during the education of researchers, including how to develop an effective curriculum. Providing a framework for research and educational institutions, this important book will be essential for anyone concerned about ethics in the scientific community.
Keywords: Policy for Science and Technology; Education

Performance Assessments for Adult Education: Exploring the Measurement Issues: Report of a Workshop - National Research Council (The National Academies Press, 2002)
In the United States, the nomenclature of adult education includes adult literacy, adult secondary education, and English for speakers of other languages (ESOL) services provided to undereducated and limited English proficient adults. Those receiving adult education services have diverse reasons for seeking additional education. With the passage of the WIA, the assessment of adult education students became mandatory-regardless of their reasons for seeking services. The law does allow the states and local programs flexibility in selecting the most appropriate assessment for the student. The purpose of the NRC's workshop was to explore issues related to efforts to measure learning gains in adult basic education programs, with a focus on performance-based assessments.
Keywords: Education